Artificial Intelligence (AI) Innovation in Driving Global Financial Inclusion: Student Program to Reduce Inequity, Support Sustainable Development Goals(SDG) 8 Through Digital Solutions and Empowering Micro and Small Businesses in the Society 5.0 Era - Wijaya, Tria Fenda Afi (Ebiz Prima Nusa, 2025)
Financial inclusion is a critical element in achieving sustainable economic growth and reducing inequality, especially among Micro and Small Enterprises (MSEs). This article examines Artificial Intelligence (AI) innovations that play a role in driving global financial inclusion, and how student programs can support Sustainable Development Goal (SDG) 8. By utilizing digital solutions, students play an active role in designing applications and platforms that improve MSEs’ access to financial services. Through a qualitative approach, this study highlights several student initiatives that have successfully improved financial literacy and credit access for MSEs. It was found that the use of AI in data analysis allows for more accurate risk assessments, reduces costs, and accelerates the financing process. As a result, student involvement in financial technology innovations not only increases inclusion but also empowers MSEs to contribute to the local economy. This article provides recommendations for stakeholders in optimizing the role of students in supporting financial inclusion and achieving SDG 8 in the Society 5.0 Era.